2017
DOI: 10.3233/prm-170436
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to support treatment options for children with swallowing and feeding disorders: A systematic review

Abstract: There is insufficient quantity of evidence to determine the effects of oral motor, sensory, and pharmaceutical therapies on functional feeding outcomes in pediatric populations. A larger body of phase 1 evidence is available that establishes the efficacy of behavioral strategies to treat some swallowing and feeding difficulties in small cohort and single subject studies. This analysis identified limited high quality (phase 4) research articles that establish the efficacy and benefit of joint nutrition and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…As detailed in Table 3, the use of more than one treatment methods was observed in every treatment study. This multi-modal finding is consistent with results of both narrative and systematic reviews identified in our literature search, many of which suggest that sensorimotor interventions for chewing dysfunction most often involve a variety of methods, including oral motor exercises, sensory stimulation, consistency changes, positioning and mealtime modifications to name a few (Arvedson, 1998;Gosa & Dodrill, 2017;Gosa, Carden, Jacks et al, 2017).…”
Section: Naturesupporting
confidence: 85%
“…As detailed in Table 3, the use of more than one treatment methods was observed in every treatment study. This multi-modal finding is consistent with results of both narrative and systematic reviews identified in our literature search, many of which suggest that sensorimotor interventions for chewing dysfunction most often involve a variety of methods, including oral motor exercises, sensory stimulation, consistency changes, positioning and mealtime modifications to name a few (Arvedson, 1998;Gosa & Dodrill, 2017;Gosa, Carden, Jacks et al, 2017).…”
Section: Naturesupporting
confidence: 85%
“…These results complement and add to prior studies in this field. Few studies have evaluated the impact of feeding interventions on improvement in symptoms and outcomes in any type of oropharyngeal dysphagia (25). Jackson showed symptom improvements from feeding interventions in a population of Down syndrome patients with aspiration (30).…”
Section: Discussionmentioning
confidence: 99%
“… 12 Level of evidence was low with only a few large randomized controlled trials published and none of these including adolescents. 12 Another review from 2020 concentrating only on management of ARFID found equally little evidence to support any particular treatment modality. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence on management of non‐organic swallowing difficulties in older children is scarce. A systematic review of articles published before the end 2015 identified 61 studies reporting intervention strategies for pediatric dysphagia covering oral motor, sensory, pharmaceutical and behavioral domains 12 . Level of evidence was low with only a few large randomized controlled trials published and none of these including adolescents 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation